Ideal mira u ustavnopravnom i upravno-pravnom poretku Bosne i Hercegovine / The Peace Ideal in Constitutional and Administrative B&H Legal Order - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The text gives a short analysis of grounding the General Framework Agreement for Peace in Bosnia and Herzegovina on UN Charter in combination with the Washington Agreement. The paper subsequently lists the UN Charter's peace provisions and Higher Representative's legal position in regard the peace preservation in B&H. The peace observing as a sine qua non of both BH and regional stability must be enhanced by amending the Constitutions of BiH, FBiH and RS. This goal can be achieved by achieved by harmonizing the a) BH Constitution (Annex IV respectively) with the general and particular international standards of UN, Council of Europe, European Union in accordance with the Bosnia and Herzegovina‟s continuity in international relations; b) the Constitutions of FBiH and RS with the BiH Constitution by abolishing the majority of first generation provisions on human rights and fundamental freedoms, and certain provisions regarding the administrative and legal order of BiH and two entities, and c) changes to the BH Constitution, the Constitutions of FBiH and RS through decisions rendered by constituent and legislative authority. The opening of a discussion relating to the reform of BH legal order in international EU organizations with whom BiH has entered into international legal relations is presented instead of conclusion in the end of the paper.